Effect of the zero-covid policy on Chinese FDI inflows and government’s response: Has the Pandemic led to distinctive paradigm change in China’s hypergrowth approach to development? - Demeure, Nicolas; Lee, Brice Tseen Fu (UI Scholars Hub, 2023)
This study examines the effects of China's zero-covid policy on its economy and investigates whether the policy reflects a broader shift in the country's development paradigm. Employing a mixed-methods approach, we analyze key macroeconomic indicators, conduct case studies of strict lockdowns, perform textual analysis of official documents, and apply the concept of fragmented authoritarianism to explore the relationship between central and local governments. The findings indicate that while the zero-covid policy has had negative economic repercussions, China's response does not signify a major departure from its pre-pandemic development paradigm. The initial success of the policy in curbing the spread of the virus attracted foreign investment, but prolonged restrictions led to increasing uncertainty and economic costs. The textual analysis reveals no significant decline in focus on economic performance, suggesting that the pandemic has not markedly shifted the importance of economic growth in China's development paradigm. However, the examination of the fragmented authoritarianism network indicates that the policy may have served as a tool for reinforcing the central party's control over local governments. Overall, this research offers a comprehensive understanding of the implications of the zero-covid policy for China's economy and development trajectory, highlighting the need for a nuanced analysis of the policy's consequences in the context of a changing global landscape.